How do personality factors associate with prosocial behavior? the mediating role of empathy - Abdullah, Alsalman Arwa; Hamsan, Hanina Halimatusaadiah; Ma'rof, Aini Azeqa (Human Resource Management Academic Research Society, 2020)
This research aims to examine the relationships between empathy, prosocial behaviour, and personality factors among Saudi undergraduate students. In total, 394 Saudi undergraduates participated in the study, which employed the prosocial behaviour scale (PBC), international personality item pool (IPIP), and Toronto empathy questionnaire (TEQ). The Pearson correlation analysis was used to investigate the associations between the research variables, while process macro analysis used to examine whether empathy mediates the association between agreeableness and prosocial behaviour. The research findings indicate that personality factors are related to empathy. Saudi undergraduates who show higher degrees of empathy would also show high degrees of prosocial behaviours. In addition, personality factors were similarly associated with prosocial behaviour. The results also show that empathy mediates the relationship between prosocial behaviour and agreeableness. The results of this study expand the existing literature review on prosocial behaviour by explaining how personality factors influence prosocial behaviour through the mediation role of empathy.